Issues in the Economic Development of Nonmetropolitan United States. Economic Development Research Report - Ledebur, Larry C.; Economic Development Administration (DOC), Washington, DC. Office of Economic Research ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
Describing issues relative to economic development in nonmetropolitan areas, this document presents narrative and tabular data re: (1) the causal forces behind economic decline in rural America (technology, shifting patterns of demand for goods and services, and changes in life styles and residential preferences); (2) the incidence and indicators of rural poverty (rural-urban differences in low income by race for 1973 and indicators of housing, average family income, education, rural outmigration, and dependence ratios); (3) issues in regional economic development (role of the market; policy orientations re: low incomes and unemployment; place prosperity vs people prosperity or migration encouragement vs regional development; equity vs efficiency or income equity vs economic efficiency; the worst "first" controversy or focus upon regions of greatest poverty vs those of greatest potential); (4) goals of economic development (possible components of a multifaceted scale to gauge economic development: efficiency and the rate of economic growth; per capita income; equity and income distribution; stability of income and employment; environmental quality; and public services access); (5) the changing context of rural economic development (selective statistical evidence in support of the assertion that society and the economy are changing structurally and qualitatively to countermand the dominant urban trend of this century). (JC)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Definitions; Differences; Economic Development; Economically Disadvantaged; Employment; Income; Life Style; Migration; Policy Formation; Political Issues; Population Distribution; Racial Differences; Regional Characteristics; Rural Areas; Rural Development; Rural Urban Differences; Social Change; Social Indicators; Tables (Data); Urban to Rural Migration; Nonmetropolitan Areas; Residential Preferences; Reports, Research